Redesigning the Authority of Autonomous Region in Geothermal Management: a Constitutional Justice Perspective - Syofyan Hadi (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
The purpose of this study is to analyse the authority of autonomous regions in geothermal management and to find a fair redesign of the division of geothermal management authority to autonomous regions. This study is a legal study with a statute, conceptual, and case approach. The primary and secondary legal materials that have been collected are then analysed normatively. The results of the study found that through the principle of the broadest possible autonomy, the central government decentralizes some concurrent government affairs to autonomous regions. One of the concurrent affairs is geothermal affairs. However, Law No. 23 of 2014 regulates the centralization of geothermal permit issuance, so that it only becomes the authority of the Central Government. In fact, this centralization is strengthened by the Constitutional Court Decision Number 11/PUU-XIV/2016. In fact, this causes injustice to autonomous regions. After all, it is contrary to Article 18 paragraph (2) and paragraph (5) and Article 18A paragraph (1) and paragraph (2) of the 1945 Constitution of the Republic of Indonesia and is inconsistent with Law No. 23 of 2014 because it only uses the principle of national strategic interests. Therefore, as an effort to provide justice for the regions, the regulation needs to be redesigned by dividing the authority to grant geothermal permits among the regions. The division of authority is carried out using the principles of accountability, externality, and efficiency by considering the location/place of the geothermal permit, users, and benefits/negative impacts of granting geothermal permits, as well as efficiency in the implementation of granting geothermal permits.